Adalberto Libera a Trento. Il palazzo per l’Istituto Nazionale delle Assicurazioni (1936–50) (TEST I libri digitali di XY, 2020)
Preface. In the shade of the Torrione d’Augusto. Adalberto Libera in Trento, words and syntaxFabio CampolongoIntroductionPiazza Venezia, Largo Porta Nuova and Via Galilei in the redesign of the city of Trento during fascismThe contribution of the National Institute of Insurance to the development of architecture in Italy between the two Wars. The case of BozenAdalberto Libera and Trento. Trentino projects of the 1930sAdalberto Libera and research on the theme of living in the 1930s and 1940sAdalberto Libera’s first projects for the INA building in Trento (1938–43)The edification (1946–50)The INA building and the new face of Largo Porta Nuova and Piazza Venezia in the 1950sAfterword. Adalberto Libera 1903 – 1963Marco MulazzaniAnnotated references and documentary sourcesAdalberto Libera's projects for the INA building: graphic reconstructionsCristina PellegattaThe INA building in Paolo Sandri’s photographs (2018)English texts. Introduction and chapters abstracts